O período de adaptação e os objetos transicionais no processo: pesquisa-intervenção em um centro de educação infantil de São Paulo - Negrão, Tatiane Peres Alves (2018)
The focus of this research is the period of adaptation and the use of transitional objects in this process. Its main objective is to analyze how the period of adaptation of infants and very small children and the usage of transitional objects during the phase of insertion of the child in the Children’s Education Center (CEI). We have listed specific objectives: to verify how the adaptation period in the CEI occurs; to observe if the nursery teachers allow the use of transitional objects; to identify the objects that infants and toddlers use; to verify possible behavior changes and reactions of those who use these objects. The universe of this research is the Children’s Education Center, located in the eastern part of the city of São Paulo. The methodology used is qualitative of the intervention type based on action research, and the instruments of data collection are: observation and recording, semi-structure interview and conversation round with four teachers working in two nursery classes. The research is based on authors of Psychoanalysis and Critical Pedagogy. The results show that the teachers made it possible for the children to use the transitional objects during the adaptation period; however, at meal times, two teachers made interventions regarding the use of pacifiers and pans because the children did not accept the meals offered and they were still crying. Sometimes, faced with the constant crying of the children, the teachers negotiated with them, collecting the transitional object, informing the child that it would be returned only when the crying ceased. Babies and very small children who used transitional objects fell asleep before other children, calmed down faster and more easily adapted to the CEI routine, demonstrating safety and comfort. These results lead us to think how much it is necessary to discuss this theme in the courses of initial and continuing teacher training, so that when entering the teaching career, teachers can understand and become more aware of the children’s needs, understanding the importance of objects especially during the period of adaptation in the CEI.